2020
DOI: 10.1038/s41598-020-67401-y
|View full text |Cite
|
Sign up to set email alerts
|

Doublecortin-like kinase 1 promotes hepatocyte clonogenicity and oncogenic programming via non-canonical β-catenin-dependent mechanism

Abstract: Chronic liver injury is a risk factor for cirrhosis and hepatocellular carcinoma (HCC). The molecular mechanisms that regulate the decision between normal injury repair and neoplastic initiation are unclear. Doublecortin-like kinase 1 (DCLK1), a tumor stem cell marker, is induced during cirrhosis and HCC. Here, we demonstrate that DCLK1-overexpressing primary human hepatocytes formed spheroids in suspension cultures. Spheroids derived from DCLK1-overexpressing hepatoma cells showed high level expression of act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Both DCLK1 and S100A9 are highly expressed in CLD, including fatty liver, cirrhosis, and hepatocellular carcinoma. To determine whether SARS-CoV-2-infected cells with high DCLK1 expression have increased viral replication, we used primary human hepatocytes (PHHs) cultured cells on thin Matrigel layers to retain plasticity and lineages ( 15 , 23 ). The ACE2 viral receptor was highly expressed under these conditions ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both DCLK1 and S100A9 are highly expressed in CLD, including fatty liver, cirrhosis, and hepatocellular carcinoma. To determine whether SARS-CoV-2-infected cells with high DCLK1 expression have increased viral replication, we used primary human hepatocytes (PHHs) cultured cells on thin Matrigel layers to retain plasticity and lineages ( 15 , 23 ). The ACE2 viral receptor was highly expressed under these conditions ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed that doublecortin-like kinase 1 (DCLK1) is induced by tissue injury and inflammation in the liver, lung, and gastrointestinal tract ( 13 , 14 ). DCLK1 is a multifunctional protein known for its involvement in clonogenicity, stemness, and tumorigenesis ( 15 18 ). It catalyzes tubulin polymerization that facilitates intracellular molecular transport and the replication of several viruses (e.g., adenoviruses, herpesviruses, and influenza viruses) ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that DCLK1 regulates migration, invasion and cell motility via activation of EMT (43), an important process for cancer initiation, cancer metastasis, and secondary tumor formation. However, expression of DCLK1 was also associated with impaired DNA repair (57,58), upregulation of WNT/b-catenin (59,60), RAS (13,61), PI3K/AKT (62) and VEGF (63,64) signaling, suggesting a multifaceted role of DCLK1 in cancer initiation and progression. Concordantly, our analysis of TCGA-HNSC dataset indicates that in HNSCC, tumors expressing higher DCLK1 mRNA levels were enriched for pathways that have been implicated in the EMT and CSC maintenance (such as NOTCH, WNT, TGFb, and hedgehog signaling), as well as for RAS and angiogenesis cascades.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of DCLK1 in primary human hepatocytes has been demonstrated to form spheroids in suspension cultures. Furthermore, these cells express high levels of β-catenin, α-fetoprotein and SOX9, suggesting that DCLK1 can induce clonogenicity in hepatoma cells ( 48 ). Table I illustrates the role of DCLK1 in three of the most prevalent types of cancer.…”
Section: Functions Of Dclk1 and Its Role In Cancermentioning
confidence: 99%